A novel bi-phase Sr-doped magnesium phosphate/calcium silicate composite scaffold and its osteogenesis promoting effect. Issue 14 (1st October 2018) - Li, Shengyi; Pu, Ximing; Chen, Xianchun; Liao, Xiaoming; Huang, Zhongbing; Yin, Guangfu
Abstract: In order to improve the osteoconductivity and the osteoinductivity of bone tissue engineering scaffold, a novel bi-phase strontium-doped magnesium phosphate/calcium silicate (Sr-MP/CSC) composite scaffold was fabricated by the self-solidifying/particulate leaching method. The bi-phase composition of the well-crystallized struvite grains wrapped by the calcium silicate floccules was propitious to the deformability and toughness of composite scaffold, and the porous structure with interconnected macropores of 100–400 µm was beneficial to supporting the tissue growth and transporting nutrients and metabolites. When the Sr-MP/CSC composite scaffolds were degraded in the simulated physiological environment, the doped strontium could be sustainably released together with Ca 2+, Mg 2+, PO4 3- and silidous ions. The proliferation and osteogenic differentiation of rat bone marrow stromal cells (BMSCs) on these composite scaffolds were obviously promoted. More valuably, the Sr-doped MP/CSC scaffolds exhibited the more obvious promotion to ALP activity, Col I and OCN expression than the un-doped MP/CSC scaffold, especially in the later stage. The results suggested that the strontium combined with calcium, magnesium and silicon could synergically promote osteogenesis, and the Sr-MP/CSC composite might be one of the promising bone tissue engineering scaffold materials.